Causal explanations for lack of pregnancy applying the common sense model of illness representation to the fertility context. Issue 10 (3rd October 2018) - Koert, Emily; Harrison, China; Bunting, Laura; Gladwyn-Khan, Misbah; Boivin, Jacky
Abstract: Objectives: The current study explored causal explanations for lack of pregnancy and association with help-seeking behaviour. Differences based on gender and country Human Development Index were examined. Design: A mixed method design was used. Main outcome measures: Data were drawn from the International Fertility Decision-Making Study, a cross-sectional study of 10, 045 individuals (1690 men; 8355 women) from 79 countries. Respondents rated to what extent they believed their lack of pregnancy was due to something they or their partner had done/not done or other factors and described their reasons for making this rating. Results: Respondents were aged 18–50 (M = 31.83) years, partnered and had been trying to achieve a pregnancy/father a child for over six months (M = 2.8 years). Men and women primarily believed their lack of pregnancy was due to medical problems or chance/bad luck. Thematic analysis of textual responses from 29.7% of the sample found that respondents focused on their personal experience or a salient life event when describing the cause of their lack of pregnancy. Women expressed more regret and helplessness about causes than men. Significant country differences were observed. Conclusions: Individuals may develop inaccurate causal explanations based on their personal experiences. Access to accurate information is necessary to facilitate timely help-seeking.